(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Task-Based Language Teaching (TBLT) is presented in this article as a learnercentered approach that promotes natural language use through real-world tasks. Drawing on practical classroom experiences across three schools and supported by recent studies, the article demonstrates how TBLT enhances speaking and writing proficiency, increases student motivation, and fosters meaningful engagement. Implementation tips for educators are also provided, highlighting how tasks can be adapted to suit different levels and contexts.